2012
DOI: 10.1074/jbc.a112.377465
|View full text |Cite
|
Sign up to set email alerts
|

The neural cell adhesion molecules L1 and CHL1 are cleaved by BACE1 protease in vivo.

Abstract: Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 0 publications
2
47
1
Order By: Relevance
“…; Zhou et al . ) has led to important insights into the molecular basis of BACE1‐dependent axon guidance. CHL1 is a type I membrane protein involved in axon outgrowth and neuronal survival (Naus et al .…”
Section: Bace1 Functions In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zhou et al . ) has led to important insights into the molecular basis of BACE1‐dependent axon guidance. CHL1 is a type I membrane protein involved in axon outgrowth and neuronal survival (Naus et al .…”
Section: Bace1 Functions In the Cnsmentioning
confidence: 99%
“…Zhou et al . () identified 13 substrates from cultured neurons under serum‐ and protein‐free conditions and used differential isotopic labeling of terminal amines and Ɛ‐amines for quantification. In contrast, Kuhn et al .…”
Section: Additional Bace1 Substrates In the Cnsmentioning
confidence: 99%
“…BACE1 knockout mice exhibit deficits in such brain functions [28,52], and it is extremely well known that AD patients display deficits in such functions as well. Interestingly, at approximately the same time, two separate studies identified two cell-adhesion associated molecules, L1 and CHL1, as BACE1 substrates [54,55]. Interestingly, at approximately the same time, two separate studies identified two cell-adhesion associated molecules, L1 and CHL1, as BACE1 substrates [54,55].…”
Section: Targeting Bace1 Therapeutically -Is It a Good Idea?mentioning
confidence: 90%
“…It is reported that BACE1 cleaves IL-1R2 but the total level of IL-IR2 is unchanged in BACE1 −/− cells [57]. Recently, evidence also suggests that BACE1 cleaves enterokinase and the neural cell adhesion molecules (L1 and CHL1) [58,59]. The broader issue of how many substrates interact with BACE1 is being explored, but research suggests that there are dozens of possibilities.…”
Section: Substrates Of Bace1mentioning
confidence: 99%